Ionic dissolution products from bioactive glass-ceramic scaffolds 45S5.2B positively modulate the in vitro cell response under conditions of hyperglycemia - Haro Durand, Luis Alberto (2019)
One of the main complications of diabetes mellitus (DM) is the failure in the process of tissue repair due to cellular dysfunction as a result of hyperglycemia. Under hyperglycemic conditions, the main cells involved in restoring the functionality and integrity of tissues are unable to migrate, proliferate, and secrete growth factors and components of the extracellular matrix, all of which is favored by altered mechanisms of glycation and oxidation. This alteration invariably contributes to failures in repair processes. Thus, it is of biomedical interest to study different therapeutic strategies to optimize the repair and/or regeneration of tissues under hyperglycemic conditions. These strategies may include the use of different biomaterials in the form of three-dimensional porous matrices, known as scaffolds. The ideal design of these scaffolds should provide temporary biocompatible mechanical support and positively modulate the cellular response. Since it has been established that boron (B) plays a role in angiogenesis and tissue repair, it can be expected that the controlled and localized release of B ions from the bioactive glass-ceramic scaffolds could represent a promising alternative therapy in regenerative medicine of vascularized tissues in patients with DM. The aim of this work was to study the in vitro cellular response of ionic dissolution products from bioactive scaffolds manufactured from the controlled crystallization of a 45S5 glass (% w/w composition: 45% SiO2, 24.5% Na2O, 24.5% CaO, and 6% P2O5) added with 2% of B2O3 (45S5.2B), in primary cultures of fibroblasts (HDF) and endothelial cells (HUVECs) grown in hyperglycemic conditions (30 mM D-glucose). The results demonstrated, for the first time, that the ionic dissolution products released from the 45S5.2B bioactive glass-ceramic scaffolds positively modulate the in vitro cellular response of fibroblasts and endothelial cells grown under hyperglycemic conditions. This was corroborated by an increased proliferative and migratory response, greater ability to form tubules in vitro and an increase in the secretion of growth factors. These findings may be relevant in vascularized tissue engineering since scaffolds obtained from the 45S5.2B bioactive glass could act as inorganic agents that positively modulate the cellular response and favor processes of tissue repair and/or regeneration in patients with DM.